PENERAPAN ASAS SEDERHANA, CEPAT, DAN BIAYA RINGAN DALAM PROSES PENYELESAIAN SENGKETA WANPRESTASI DI PENGADILAN NEGERI DENPASAR - Ni Putu Sri Wahyuni Purnama Dewi; Suwarjo; Ratna Artha Windari (Universitas Pendidikan Ganesha, 2026)
The principle of simple, speedy, and low-cost justice is a fundamental element in ensuring effective civil dispute resolution, including cases of breach of contract. This study aims to analyze the implementation of these principles in resolving breach of contract disputes at the Denpasar District Court, identify the factors affecting their effectiveness, and formulate optimization efforts. This research employed an empirical juridical approach with a descriptive qualitative method. Primary data were obtained through interviews with a judge of the Denpasar District Court, while secondary data were collected through literature and legal document reviews. The findings indicate that the implementation of these principles has been supported by the adoption of e-Court and electronic litigation, which improve administrative efficiency and reduce litigation costs. However, their effectiveness is influenced by the parties' good faith, compliance with the court calendar, the success rate of mediation, infrastructure limitations, and the outdated civil procedural law. Therefore, strengthening digital infrastructure and reforming civil procedural law are essential to optimize judicial services.